Pros and cons of university ranking - Feyen, Jan (Maskana, 2021)
Ranking of universities has become over the past two decades a common practice and the institutions’ interest in ranking at national and international level is only increasing. Universities, analogous to the industry, increasingly use their ranking to highlight their quality and excellence, with the objective to increase its visibility leading to a positive impact on the attraction of students and faculty, and cooperation with the public and private sector. Various studies showed that the ease of fund raising, international cooperation, recruitment of international and local students, graduate employment, and the cooperation with the private and public sector are positively affected by the institution’s ranking. Through this editorial note, the author, who has a vast experience in university management, makes a brief analysis not only of the pros but also of the cons of this type of rankings, providing insights on the essential aspects to take into account from this information and also on how to correctly interpret the data from this useful management tool, especially in the context of the reality of our Latin American universities.